A Return to the Wild: Root Exudates and Food Security - Preece, Catherine; Peñuelas, Josep (Trends in plant science, 2020)
Challenges to food security under conditions of global change are forcing us to increase global crop production. Focussing on belowground plant traits, especially root exudation, has great promise to meet this challenge. Root exudation is the release of a vast array of compounds into the soil. These exudates are involved in many biotic and abiotic interactions. Wild relatives of crops provide a large potential source of information and genetic material and have desirable traits that could be incorporated into modern breeding programs. However, root exudates are currently underexploited. Here, we highlight how the traits of root exudates of crop wild relatives could be used to improve agricultural output and reduce environmental impacts, particularly by decreasing our dependence on pesticides and fertilisers. Root exudates are the compounds that roots release into the soil.Root exudates show a large amount of variation in composition between species.Crop wild relatives contain different root exudate traits compared with crops.Exploitation of root exudate traits in crop wild relatives offers opportunities to reduce the use of fertilisers and pesticides.